Challenges and opportunities of high-yielding fodder production in coastal Bangladesh - Debnath, Manik; Ahmed, Sharif; Haque, Abdul; Sultana, Nasrin; Bhandari, Humnath (International Rice Research Institute, 2025)
"The livestock production sector plays a crucial role in ensuring nutrition security in Bangladesh. It provides high-quality animal protein, including meat, milk, and eggs, which helps combat malnutrition and generates income for impoverished rural households. By improving access to animal-source foods through small-scale, household-level farming, livestock enhances the dietary intake of essential micronutrients, particularly for vulnerable groups such as young children and pregnant women. Additionally, livestock contributes to agricultural productivity by offering manure, which further supports food security. Livestock is directly or indirectly linked to all 17 SDGs and faces many challenges to achieve sustainability while responding to a significant increase in demand for animal products. In 2025, the livestock sector's contribution to Bangladesh's GDP is approximately 1.81%. This sub-sector has a growth rate of 3.19% and accounts for 16.54% of the total agricultural GDP. The sector also provides direct employment to around 20% of the population, with an additional 50% partially engaged. During 2024-25, the total Livestock Population in Bangladesh was 57.97 M (Cattle: 25.17 M, Buffalo: 1.53 M, Sheep: 3.98 M, Goat: 27.29 M). GDP Volume was 91,036 crore Taka. Demand for milk was 162.33 lakh metric tons (250 ml/day/head) and production was 155.38 lakh metric tons. Demand for meat was 77.92 lakh metric tons (120 gm/day/head), and production was 89.54 lakh metric tons. (Source: BBS 2024- 25). Raising livestock is a better livelihood option for households in coastal areas. Cattle, goats, and sheep are major sources of family income, nutrition, food security, and social status. Although the livestock population in the region is relatively high, productivity remains low due to poor health caused by a lack of green fodder and disease. Feed and fodder are agricultural terms that refer to animal feed, while fodder crops are plants grown specifically for livestock. Fodder plays a crucial role in maintaining animal health, boosting productivity, and ensuring food security. In Bangladesh, the demand for high-quality fodder is increasing due to the growing livestock population, a shortage of grazing land, and the need for more profitable farming practices. Providing high-quality fodder leads to better milk and meat production, enhances animal immunity, and can reduce costs for farmers by lowering their dependence on expensive imported feeds. This rising demand is also creating income-generating opportunities in fodder cultivation. The production of fodder is gaining momentum, yet the country still faces significant deficits: over 40% in dry matter, 65% in crude protein, and 60% in metabolizable energy. The recent growth rate in livestock is not keeping pace with the demand for feed and fodder. The development of livestock relies heavily on improving animal nutrition through better feeding practices and increased availability of fodder. Currently, about 90% of the cattle feed supply consists of poor-quality roughage, primarily rice straw, along with a small amount of green grass and minimal concentrate. Rice straw is lacking in readily fermentable carbohydrates, protein, minerals, and vitamins. Consequently, animals that rely solely on rice straw exhibit low growth rates in both milk and meat production, achieving only about 10% of their genetic potential. To address this issue, it is often recommended to supplement a straw-based diet with a sufficient amount of green grass to meet the nutritional needs of the animals. Livestock are vital in Bangladesh's coastal areas, providing a key source of nutrition and income, particularly as the region is vulnerable to climate-related risks that affect crop production. They offer a diversified livelihood through meat, milk, and eggs, create jobs, and provide organic manure for farming, especially during the lean agricultural season. The importance of livestock is underscored by the fact that a significant portion of the land in the coastal zone is affected by salinity, making it unsuitable for some crop farming, and that many farmers lack the resources to grow fodder. Salinity issues significantly hinder both agricultural and economic development in the coastal belt of Bangladesh. The saline environment adversely affects crop production throughout the year, as the organic matter content of the coastal soils is low, ranging from 1.0% to 1.5%. Furthermore, nutrient deficiencies, particularly of nitrogen (N) and phosphorus (P), are common in saline soils. Consequently, the decline in food crop production in this region has a substantial impact on the national economy of Bangladesh. In addition, increased salinity leads to a shortage of grazing land and fodder crops for livestock, forcing communities to seek alternative natural resources to compensate for the protein deficiency that arises from reduced livestock production. Research studies have documented a noticeable shortage of milk and cattle in the coastal areas as a result of these challenges. Coastal areas of Bangladesh face a severe shortage of improved fodder, driven by salinity intrusion, limited arable land, and a lack of awareness and investment in fodder cultivation. This shortage threatens livestock health and productivity, impacting livelihoods in the region. Fodder cultivation is constrained by land scarcity and high soil salinity, with farmers primarily focusing on food crops. Though livestock rearing is important, it struggles due to insufficient fodder land and seasonal salinity spikes. Efforts are underway to implement climate-smart agricultural practices, such as using salinity-resistant varieties. Most farmers rely on dry rice straw as the main feed, while a lack of grazing land exacerbates the feed crisis, particularly during the dry season."